Partisan Bias and Its Discontents. (March 2019) - Ditto, Peter H.; Clark, Cory J.; Liu, Brittany S.; Wojcik, Sean P.; Chen, Eric E.; Grady, Rebecca H.; Celniker, Jared B.; Zinger, Joanne F.
Baron and Jost (this issue, p. 292) present three critiques of our meta-analysis demonstrating similar levels of partisan bias in liberals and conservatives: (a) that the studies we examined were biased toward finding symmetrical bias among liberals and conservatives, (b) that the studies we examined do not measure partisan bias but rather rational Bayesian updating, and (c) that social psychology is not biased in favor of liberals but rather toward creating false equivalencies. We respond in turn that (a) the included studies covered a wide variety of issues at the core of contemporary political conflict and fairly compared bias by establishing conditions under which both liberals and conservatives would have similar motivations and opportunities to demonstrate bias; (b) we carefully selected studies that were least vulnerable to Bayesian counterexplanation, and most scientists and laypeople consider these studies demonstrations of bias; and (c) there is reason to be vigilant about liberal bias in social psychology, but this does not preclude concerns about other possible biases, all of which threaten good science. We close with recommendations for future research and urge researchers to move beyond broad generalizations of political differences that are insensitive to time and context.